8(8a+8)+2(8a+6)=-4

Simple and best practice solution for 8(8a+8)+2(8a+6)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(8a+8)+2(8a+6)=-4 equation:


Simplifying
8(8a + 8) + 2(8a + 6) = -4

Reorder the terms:
8(8 + 8a) + 2(8a + 6) = -4
(8 * 8 + 8a * 8) + 2(8a + 6) = -4
(64 + 64a) + 2(8a + 6) = -4

Reorder the terms:
64 + 64a + 2(6 + 8a) = -4
64 + 64a + (6 * 2 + 8a * 2) = -4
64 + 64a + (12 + 16a) = -4

Reorder the terms:
64 + 12 + 64a + 16a = -4

Combine like terms: 64 + 12 = 76
76 + 64a + 16a = -4

Combine like terms: 64a + 16a = 80a
76 + 80a = -4

Solving
76 + 80a = -4

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-76' to each side of the equation.
76 + -76 + 80a = -4 + -76

Combine like terms: 76 + -76 = 0
0 + 80a = -4 + -76
80a = -4 + -76

Combine like terms: -4 + -76 = -80
80a = -80

Divide each side by '80'.
a = -1

Simplifying
a = -1

See similar equations:

| 44=-3(9-7m)-8(5-9m) | | 44=-7(1-7m)-2(8-9m) | | 3.5/6.3=x | | 18=-7(1-5m)-2(8-3m) | | X^3-19x-30=0 | | -5p-3q-2p+4q-3p+3q= | | 199-90x=1819 | | (x-6)+2=7 | | [x-6]+2=7 | | 4p-20=76 | | 2.50+3.75x=40 | | 3.00x+150=177 | | x-3.00=47 | | 50+60x=890 | | 3a+4b+5a-2b-4a-b= | | 50*200=x | | 23-4x=7 | | 10y^3-6y+2-2y+5= | | 2m+5=10(3m-10) | | 2x^2+8x+3+x^2-5x-2= | | 2m+5-3m-7= | | 3x+4x:8x=338 | | 3x+4x:8x=388 | | 3(2x+1)-4(x-1)=13 | | 7x-(8-17x)x=18 | | a-8+3a=12 | | 2x^2-16x=8 | | 3x-3y-4x= | | 3x-y-4x-3y= | | 3a-2b-2a+5b= | | -8x=-5 | | 20-x(4+1)=5x |

Equations solver categories